Evaluasi Kuantitas Limbah Medis Sebelum Dan Selama Pandemi Covid-19 Sebagai Pengendalian Pencemaran Di Rumah Sakit ‘Aisyiyah Bojonegoro - Sukir Sukir; Rizky Rahadian Wicaksono; Gading Wilda Aniriani (Universitas Islam Lamongan, 2023)
AbstractBased on Presidential Decree Number 12 of 2020 concerning the Determination of Non-Natural Disasters in the spread of Corona Virus Disease 2019 (Covid-19) as a National Disaster, of course there will be an increase in liquid waste from the use of personal protective equipment which can be a source of disease transmission so that if it is not managed properly will have a major impact on environmental sustainability in every country, including Indonesia. By understanding the increase in waste, control in hospitals is very necessary. The purpose of this study was to find out how the quantity of infectious medical waste at the Hospital 'Aisyiyah Bojonegoro before and during the Covid-19 pandemic. This study uses a non-experimental method with a descriptive evaluation design. Data collection techniques in this study using observation (observation), interviews, documentation or data collection The results showed that the quantity of infectious medical waste before the Covid-19 pandemic could be accumulated at 21,995 kg. Meanwhile, after the Covid-19 pandemic, 80,607 kg were accumulated. The conclusion that can be drawn is that there is an increase in the quantity of infectious medical waste by 72.71%.Keywords: Quantity, Infectious, Waste AbstrakBerdasarkan Keputusan Presiden Nomor 12 Tahun 2020 tentang Penetapan Bencana Non Alam pada penyebaran Corona Virus Disease 2019 (Covid-19) sebagai Bencana Nasional, tentu akan meningkatkanan limbah infeksius dari bekas penggunaan alat pelindung diri yang dapat menjadi sumber penularan penyakit sehingga apabila tidak dilakukan pengelolaan dengan baik akan berdampak besar bagi kelestarian lingkungan masyarakat di setiap negara termasuk Indonesia. Dengan memahami adanya dampak peningkatan limbah, pengendalian pencemaran di Rumah Sakit sangat diperlukan. Tujuan penelitian ini untuk mengetahui bagaimana kuantitas limbah medis yang bersifat infeksius di Rumah Sakit ‘Aisyiyah Bojonegoro sebelum dan selama pandemi Covid-19. Penelitian ini menggunakan metode non eksperimen dengan rancangan deskriptif evaluasi. Teknik pengumpulan data pada penelitian ini menggunakan pengamatan (observasi), wawancara, dokumentasi atau pengambilan data. Hasil penelitian menunjukkan kuantitaslimbahmedis infeksius sebelum pandemi Covid-19 dapat diakumulasikan sebesar 21.995 kg. Sedangkan sesudah pandemi Covid-19 diakumulasikan sebesar 80.607 kg. Kesimpulan yang dapat diambil ialah adanya kenaikan jumlah kuantitas limbah medis infeksius sebesar 72,71 %.Kata kunci: Kuantitas; Infeksi; Limbah